Angiogenic Squamous Dysplasia in Bronchi of Individuals at High Risk for Lung Cancer - Keith, R L; Miller, Y E; Gemmill, R M; Drabkin, H A; Dempsey, E C; Kennedy, T C; Prindiville, S; Franklin, W A (Clinical cancer research, 2000)
Lung carcinogenesis is assumed to be a multistep process, but detailed understanding of the sequential morphological and molecular changes preceding invasive lung cancer remains elusive. To better understand early lung carcinogenesis, we initiated a program of fluorescence bronchoscopy in smokers at high risk for lung cancer. In the bronchial biopsies from these subjects, we observed a unique lesion consisting of capillary blood vessels closely juxtaposed to and projecting into metaplastic or dysplastic squamous bronchial epithelium, angiogenic squamous dysplasia (ASD). Serial sections of the capillary projections confirmed that they represent intramucosal capillary loops. Microvessel density in ASD was elevated in comparison to normal mucosa ( P = 0.0003) but not in comparison to other forms of hyperplasia or dysplasia. ASD thus represents a qualitatively distinct form of angiogenesis in which there is architectural rearrangement of the capillary microvasculature. Genetic analysis of surface epithelium in a random subset of lesions revealed loss of heterozygosity at chromosome 3p in 53% of ASD lesions. No confirmed p53 mutations were identified. Compared with normal epithelium, proliferative activity was markedly elevated in ASD lesions. ASD occurred in 54 of 158 (34%) high-risk smokers without carcinoma and in 6 of 10 patients with squamous carcinoma who underwent fluorescence bronchoscopy. One early-stage invasive carcinoma was noteworthy for the occurrence of ASD juxtaposed to invasive tumor. Seventy-seven (59%) of the ASD lesions were detected by abnormal fluorescence alone. Twenty bronchial sites (11 patients) were rebiopsied 1 year after the initial diagnosis. At nine (45%) of these sites, the lesion was found to persist. The lesion was not present in biopsies from 16 normal nonsmoker control subjects. The presence of this lesion in high-risk smokers suggests that aberrant patterns of microvascularization may occur at an early stage of bronchial carcinogenesis.